Association of Psychological Wellbeing with Healthy Pregnancy, Maternal and Neonatal Outcomes - Muhammad Muslim Khan, Fatima, Muhammad Kashif, Sedra Tul Muntaha, Naila, Hemasa Gul, (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Psychological issues have a significant effect on pregnant women's health before, during, and after childbirth and can cause a number of issues. Aim: The aim of this study was to explore the association of psychological wellbeing with healthy pregnancy, maternal and neonatal outcomes Material and method: The present prospective study was carried out at the department of Psychiatry and Department of Obstetrics and Gynecology, Bacha Khan Medical College Mardan Medical Complex Mardan from July 2022 to December 2022 after taking permission the ethical committee of the hospital. Pregnant women of 1st 2nd and 3rd trimester of different age groups (ranged 17-38 years) who visited the gynecology and antenatal department were included in this study. Rasoft calculator was used to determine the sample size and was determined to be 300. The Kupposwami scale was used to measure socioeconomic status. The participant’s average level of satisfaction with their life was measured using the Satisfaction with Life Scale. The WiP and SWLS scales were examined using the appropriate techniques. Cross-tabulation and the paired sample t test were used to examine the relationship between the two variables. The risk assessment between psychiatric problems and adverse pregnancy results was done using the odds ratio test. Using the chi-square test, the significance of the mean difference was examined, with the p-value of less than 0.05 being considered significant. Results: A total of 300 pregnant women were examined in this study. The mean age of the study population was 28.5 ± 7.5(ranged 17-38) years. According to their trimester, participants were classified. The average SWL score was 11.10 ± 8.1, indicating a low level of life satisfaction. The most often reported maternal outcome was emergency cesarean section 33.0%, followed by induced labor22%, and preterm labor15%. Neonatal outcomes revealed that after birth Excessive hospitalization observed in 33 (1%) cases, respiratory problems was noted in 18 (6%) cases, low birth weight was seen in 2.3%. Maternal outcomes were positively correlated with pre-term labor, hemorrhage, and emergency caesarian sections, while neonatal outcomes were positively correlated with SGA, excessive hospitalization, and neonatal mortality. Conclusion: The present study concluded that maternal mental health distress has negative effect on both the health of the mother and neonate. Keywords: Association; Psychological Wellbeing; Pregnancy; Maternal; Neonatal.